2018
DOI: 10.1177/0361684317752643
|View full text |Cite
|
Sign up to set email alerts
|

Maybe She Is Relatable

Abstract: In the current research, we explored whether informing women about gender bias in science, technology, engineering, and mathematics (STEM) would enhance their identification with a female scientist, and whether this increased identification would in turn protect women from any adverse effects of gender bias information. We found that, relative to a control information condition, gender bias information promoted beliefs that a successful woman (but not a man) scientist had encountered bias, and encouraged ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 68 publications
3
24
0
Order By: Relevance
“…Previous research has found that workplace sexism leads to a reduced sense of belonging in the workplace among women (Richman et al, 2011;Rubin, Subašić, Giacomini, & Paolini, 2017;Stout & Dasgupta, 2011), most likely because workplace sexism represents a form of bullying, rejection, and ostracism by men against their female co-workers (e.g., Smart Richman & Leary, 2009). Similar results have been found in the case of women in male-dominated science, technology, engineering, and mathematics degrees at university (e.g., Lawson, Kooiman, & Kuchta, 2017;Moss-Racusin, Sanzari, Caluori, & Rabasco, 2018;Pietri, Johnson, Ozgumus, & Young, 2018).…”
Section: Sense Of Belonging As a Mediatorsupporting
confidence: 83%
“…Previous research has found that workplace sexism leads to a reduced sense of belonging in the workplace among women (Richman et al, 2011;Rubin, Subašić, Giacomini, & Paolini, 2017;Stout & Dasgupta, 2011), most likely because workplace sexism represents a form of bullying, rejection, and ostracism by men against their female co-workers (e.g., Smart Richman & Leary, 2009). Similar results have been found in the case of women in male-dominated science, technology, engineering, and mathematics degrees at university (e.g., Lawson, Kooiman, & Kuchta, 2017;Moss-Racusin, Sanzari, Caluori, & Rabasco, 2018;Pietri, Johnson, Ozgumus, & Young, 2018).…”
Section: Sense Of Belonging As a Mediatorsupporting
confidence: 83%
“…Previous research has found that workplace sexism leads to a reduced sense of belonging in the workplace among women (Richman et al, 2011;Rubin, Subašić, Giacomini, & Paolini, 2017;Stout & Dasgupta, 2011), most likely because workplace sexism represents a form of bullying, rejection, and ostracism by men against their female co-workers (e.g., Smart Richman & Leary, 2009). Similar results have been found in the case of women in maledominated science, technology, engineering, and mathematics degrees at university (e.g., Lawson, Kooiman, & Kuchta, 2017;Moss-Racusin, Sanzari, Caluori, & Rabasco, 2018;Pietri, Johnson, Ozgumus, & Young, 2018).…”
Section: Sense Of Belonging As a Mediatorsupporting
confidence: 54%
“…Overwhelming evidence indicates that the gender gap in science is a complex phenomenon deeply affecting society, economics and science advancement (Ely, Ibarra & Kolb, 2011;Madsen & Andrade, 2018;Hogue & Lord, 2007;Pietri et al, 2018). The gender gap in the scientific, technological, engineering and mathematical (STEM) disciplines is a disparity of how different genders enter in and progress through a career in science (Shapiro & Williams, 2012).…”
Section: Recent Literature Identifies a Link Between The Gender Gap Amentioning
confidence: 99%